2014
DOI: 10.1002/jcla.21669
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neutrophil to Lymphocyte Ratio With Presence and Severity of Gastritis Due toHelicobacter pyloriInfection

Abstract: The present study indicated, for the first time, a significant correlation between HP infection and inflammation on the basis of NLR, a simple and reliable indicator of inflammation. Furthermore, there is an increase in NLR as the severity of gastritis with HP increases. This elevated ratio gets normalized with treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 17 publications
2
56
4
1
Order By: Relevance
“…Our study showed that an NLR cutoff value of 5.4 is significant in differentiating between cases of acute bacterial tonsillitis with DSNI and those without DNSI; this is similar to the value reported by previous studies in which NLR was used as an index in diagnosing H. pyroli associated gastritis, acute appendicitis, psoriasis and infective endocarditis [20][21][22][23]. Another expected finding was that the WBC count was also positively correlated with acute bacterial tonsillitis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study showed that an NLR cutoff value of 5.4 is significant in differentiating between cases of acute bacterial tonsillitis with DSNI and those without DNSI; this is similar to the value reported by previous studies in which NLR was used as an index in diagnosing H. pyroli associated gastritis, acute appendicitis, psoriasis and infective endocarditis [20][21][22][23]. Another expected finding was that the WBC count was also positively correlated with acute bacterial tonsillitis.…”
Section: Discussionsupporting
confidence: 87%
“…Sen et al studied 138 patients with psoriasis and stated that the NLR levels were also significantly higher in the psoriasis patients, and that the NLR levels increased with increase in the psoriasis area and severity index score [20]. Farah and Khamisy-Farah studied 50 patients with Helicobacter pylori infection and found a significant correlation between H. pyroli infection and inflammation on the basis of the NLR value; furthermore, NLR increased as the severity of gastritis associated with the infection increased [21]. With regard to NLR and infections, a recent study by İshizuka et al has also assessed its relationship with gangrenous appendicitis based on an analysis of 314 patients who had undergone open appendectomy; they found that NLR has a significant association with gangrenous appendicitis and disease severity in patients undergoing appendectomy [22].…”
Section: Discussionmentioning
confidence: 94%
“…Neutrophil:lymphocyte ratio (NLR), which has become one of the most popular biomarkers in biological and medical research in recent years, has been shown to correspond to numerous chronic inflammatory diseases (9,10). NLR is both accessible and affordable, and it thus has been increasingly used in clinical trials and research studies; however, few studies have examined the relationship between NLR and T2D (11), and whether NLR is associated with T2D is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Zahorec [7] has shown that there is a correlation between the severity of the clinical course of seriously ill patients and the degree of neutrophilia and lymphopenia. Recent studies have shown that NLR values are highly associated with the prognosis of diseases related to inflammation [8,9]. High NLR values have also been shown to be referring to the poor prognosis in different types of cancers [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%